Quantification of ion migration in CH3NH3PbI3 perovskite solar cells by transient capacitance measurements. Issue 7 (24th April 2019) - Futscher, Moritz H.; Lee, Ju Min; McGovern, Lucie; Muscarella, Loreta A.; Wang, Tianyi; Haider, Muhammad Irfan; Fakharuddin, Azhar; Schmidt-Mende, Lukas; Ehrler, Bruno
Abstract : We quantify activation energy, concentration, and diffusion coefficient of mobile ions in MAPbI3 perovskite solar cells using transient ion-drift measurements. Abstract : Ion migration in halide perovskite films leads to device degradation and impedes large scale commercial applications. We use transient ion-drift measurements to quantify activation energy, diffusion coefficient, and concentration of mobile ions in methylammonium lead triiodide (MAPbI3 ) perovskite solar cells, and find that their properties change close to the tetragonal-to-orthorhombic phase transition temperature. We identify three migrating ion species which we attribute to the migration of iodide (I − ) and methylammonium (MA + ). We find that the concentration of mobile MA + ions is one order of magnitude higher than the one of mobile I − ions, and that the diffusion coefficient of mobile MA + ions is three orders of magnitude lower than the one for mobile I − ions in our samples. This quantification of mobile ions in MAPbI3 will lead to a better understanding of ion migration and its role in operation and degradation of perovskite solar cells.